Homing of translocated native Indian pythons in Moyar River Valley, South India - Vishnu, C.S.; Ramesh, Chinnasamy; Pittman, Shannon; Thirumurugan, Vedagiri; Talukdar, Gautam; Ashokan, Krishnamurthy; Arunlal, P.G.; Naganathan, Veerabadran (Heliyon, 2024)
Homing is often a critical aspect of an animal's behavioural and spatial ecology. Translocation is considered to be a wildlife management strategy that could reduce human-wildlife confrontation, but this strategy may not be effective if animals attempt to home to their original capture location. Translocation of animals from sites where possible human-wildlife interaction occurs is a widespread but controversial intervention to resolve conflicts. In India, snakes are often the subject of such translocations, but there is a paucity of information on the behaviour of translocated snakes compared to resident snakes. The Indian python (Python molurus), one of the largest carnivores in the Indian subcontinent, is classified as Near Threatened by the IUCN. We conducted a two-year radio-tracking study (December 2018 to December 2020) on the movements of 14 adult Indian pythons in the Moyar River Valley, within the Sathyamangalam and Mudumalai Tiger Reserves. Eleven of the 14 pythons were translocated 0.28–55.7 kms from their capture locations, while 3 pythons were not translocated: 6 were translocated short distances (<5 km from capture; range 0.28–4.67 kms), 2 were translocated to medium distances (9–11 kms from capture location), and 3 were translocated to long distances (21–55.7 kms from capture location). Four of the six snakes translocated short distances all returned to within 500 m of their original capture locations, and all 6 returned over 60 % of the translocated distance to the initial capture location. Of the two snakes translocated medium distances, both returned to within 1.1 km of the capture location (∼90 % of the distance home). None of the three snakes that were translocated long distances successfully returned to their capture locations. Translocated pythons exhibited greater net movement distances than resident snakes within the first 2 months of release. Based on these results, long-distance translocation may be an effective strategy to minimize human-python conflict, while short or medium distance translocation is unlikely to be successful. However, more research is needed about the long-term survival of translocated snakes as well as soft-release methodologies that could prevent aberrant movement behaviour directly following release. [Display omitted]